Graphene oxide for gas detection under standard humidity conditions. (25th September 2015) - Donarelli, Maurizio; Prezioso, Stefano; Perrozzi, Francesco; Giancaterini, Luca; Cantalini, Carlo; Treossi, Emanuele; Palermo, Vincenzo; Santucci, Sandro; Ottaviano, Luca
Abstract: Graphene oxide (GO) synthesis is the easiest way to functionalize graphene, preserving the high graphene surface to volume ratio. Therefore, GO is a promising candidate for gas sensing applications. In this paper, an easy-to-fabricate and high sensitivity GO-based gas sensor is proposed. The device is fabricated by drop-casting a solution of GO flakes dispersed in water on a prepatterned Si3 N4 substrate with 30 μ m spaced Pt electrodes. The sensing material has been studied using scanning electron microscopy and x-ray photoelectron spectroscopy. The large lateral dimensions of the flakes (tens of microns) allow single GO flake to bridge adjacent electrodes. The high quality of the synthesized flakes results in the gas sensor high sensitivity to and low detection limit (20 ppb) of NO2 . The gas sensor response to NO2 has been studied in various relative humidity environments and it is demonstrated not to be affected by the presence of water vapor. Finally, the gas sensor responses to acetone, toluene, ethanol, and ammonia are reported.